Sandstone Diagenesis: Establishing Threshold Temperature and Depth of Porosity Deterioration, Penyu Basin and Tenggol Arch, Offshore Peninsular Malaysia - Franz L. Kessler; John Jong (Ikatan Ahli Geologi Indonesia, 2018)
A review of clastic sandstone reservoirs from the Penyu Basin and Tenggol Arch area has revealed that the deepest, stratigraphically oldest and potentially overpressured reservoirs are affected by diagenetic alteration of reservoir mineral components. There is a marked discrepancy between measured reservoir temperature and calculated reservoir temperature based on vitrinite reflectance data in several investigated wells. Assuming a relatively constant temperature gradient in the basin during the Pliocene to recent time, quartz cementation started at a paleo-depth of ca. 2000m tvdss or 105°C, and porosity was mostly destroyed at a depth of ca. 3000m tvdss and 130°C. This said, there is a strong stratigraphic correlation between pre-Oligocene sediments with high vitrinite reflectivity readings, and a strongly elevated contemporaneous temperature gradient. Therefore, the scope for deep oil and gas drilling maybe reduced in at least some parts of the basin, where oil is found locked in diagenetically altered pore spaces. In addition, geological data also suggest that the Penyu Basin is very complex and may have stronger affiliation with pull-apart rather than with rift basins.